Global colorectal cancer screening programs and coverage rate estimation: an evidence synthesis - Yuqing Chen; Yuelun Zhang; Yike Yan; Jingjing Han; Li Zhang; Xinran Cheng; Bin Lu; Na Li; Chenyu Luo; Yueyang Zhou; Kai Song; Motoki Iwasaki; et al. (Journal of Translational Medicine)
Abstract Screening is effective in reducing the disease burden of colorectal cancer, with participation and coverage rates being key determinants of its effectiveness. This systematic review aims to provide a comprehensive assessment of colorectal cancer screening program characteristics and global screening coverage rates. We conducted a systematic literature search in the PubMed and Embase databases from inception to March 2025. Grey literature was obtained from screening program websites and relevant reports. Studies reporting nationwide colorectal cancer screening coverage were eligible for our analysis. A comprehensive overview of essential information and the most recent coverage rates for global screening programs were reported. Temporal trend analyses of coverage rates and subgroup analyses by sex and age were performed. Our results encompassed 45 countries with established national screening programs, among which 33 of them having retrieved coverage rates. Population-based screening programs were predominantly conducted in Europe (25/39), with fecal occult blood testing being the most commonly used modality (38/39). The reported latest screening coverage rates varied greatly across countries, ranging from 1.0% (China, 2020) to 79.4% (Finland, 2021). The coverage of screening program differed slightly between men and women in most countries (men: IQR, 25.3–52.7%; women: IQR, 23.0–65.1%), and coverage increased with age. Temporal trend analysis in 14 countries showed that the majority exhibited increasing or stable screening coverage rates. These findings highlight significant disparities in CRC screening implementation worldwide. Targeted efforts to improve participation and expand coverage are essential, particularly in countries with a high disease burden.